Challenges of halogenated polycyclic aromatic hydrocarbons in foods: Occurrence, risk, and formation. (January 2023) - Li, Wei; Wu, Shimin
Abstract: Background: According to the relative potency (REP) of Benzo[a]pyrene (BaP), halogenated polycyclic aromatic hydrocarbons (XPAHs) exhibit more complex structures and higher toxicities than their parent polycyclic aromatic hydrocarbons (PPAHs) and thus may pose a greater threat to food safety and human health. Scope and approach: The present review focuses on the publications of XPAHs in food materials and products including drinking water, unprocessed food materials, and processed foods. We summarized the profiles of XPAHs in foods and evaluated the health risks of XPAH exposure to humans via dietary intake. Moreover, the formation mechanism and prevention advice related to foods were summarized and proposed. Key findings and conclusions: Based on existing publications, the incremental lifetime cancer risk (ILCR) of XPAH exposure for humans through the dietary intake of the individual food matrix, including cereal, pork, seafood, vegetables, milk, oil, and drinking water, were all below the unacceptable risk (10 −4 ) level. However, the maximum cumulative risks in terms of the combined of XPAHs and PPAHs exhibited unacceptable risk (2.1 × 10 −4 ) for humans via dietary intake of multiple food matrices. XPAH contamination in food not only can originate from the environment directly but also may derive from the reaction between PPAHs and Cl − during food processing and storage. Moreover, risks can be reduced both by inhibiting XPAH generation during processing and by reducing the amount of the aromatic hydrocarbon receptor (AhR) that induces CYP1A1. These findings can provide a reference for the control and inhibition of XPAH generation during food processing, and therefore reduce the associated risks. Graphical abstract: Image 1 Highlights: The combined ILCR of XPAHs and PPAHs reaches an unacceptable risk level (>10 −4 ). Halogenation of PPAHs in foods can be initiated by PAH., Cl, and OH pathways. XPAHs with higher MW and halogenation tend to be more bioaccumulative. Temperature, light, and salt are dominant contributors to XPAH formation during food processing. Antioxidants can inhibit the formation of XPAHs and protect cells from DNA damage.